Agroforestry, livestock, fodder production and climate change adaptation and mitigation in East Africa: issues and options - Dawson, Ian K.; Carsan, S.; Franzel, Steven; Kindt, Roeland; Breugel, P. van; Graudal, Lars; Lillesø, Jens-Peter B.; Orwa, C.; Jamnadass, Ramni H. (World Agroforestry Centre, 2014)
Agroforestry and livestock-keeping both have the potential to promote anthropogenic climate changeresilience, and understanding how they can support each other in this context is crucial. Here, we discuss relevant issues in East Africa, where recent agroforestry interventions to support livestockkeeping have included the planting of mostly-exotic tree-fodders, and where most parts of the region are expected to become drier in the next decades, although smaller areas may become wetter. Wider cultivation and improved management of fodder trees provides adaptation and mitigation opportunities in the region, but these are generally not well quantified and there are clear opportunities for increasing productivity and resilience through diversification, genetic improvement, improved farm-input delivery and better modelling of future scenarios. We relate, and illustrate with the example of current- and future-climate tree species distribution modelling, important areas for future research.